The Proactive Approach--Is it Worthwhile? A Prospective Controlled Ergonomic Intervention Study in Office Workers - Laestadius, J. G. (2012)
OBJECTIVE: Does proactive ergonomics program enhance office worker health and productivity? METHOD: The investigation was conducted in connection with the move of 1500 office staff to a building with improved ergonomics. It was focused on associations between workstation features, working postures, musculoskeletal pain symptoms, and eye strain before and 18 months after implementation of a proactive ergonomic program. The outcomes were compared between the intervention and a similar reference group. RESULTS: Associations between improvement of postures and less musculoskeletal pain and eye strain were confirmed. A cross association between several features and postures and improved symptoms was noted, along with improved productivity. CONCLUSION: The study suggests that a proactive program adhering to the OSHA recommendations needs to include an individual workstation assessment to be effective in reducing symptoms and increasing productivity.